Change of Soil Biomass Carbon Microorganism in Ultisols Soil Due to Application of Humic Acid and TSP Fertilization - Henrie Buchari; Tri Untari; Ainin Niswati; Sunyoto Sunyoto (JOURNAL OF TROPICAL SOILS, 2021)
Soil biomass carbon microorganism (C-mic) is one indicator of soil fertility. The application of humic acid, vermicompost aqueous extract, and TSP fertilization applied to the soil will affect the activity of soil microorganisms. This research aimed to study the effect of humic acid, vermicompost extract, and TSP fertilization on C-mic. The first factor was the application of humic acid (h), namely, without humic acid, commercial origin, and humic acid-like from watery extract vermicompost. The second factor is TSP fertilization (p) divided into four dose levels: without TSP fertilizer, TSP fertilizer 100 kg ha-1, TSP fertilizer 200 kg ha-1, and TSP fertilizer 300 kg ha-1. Data were analyzed by analysis of variance and continued with the Least Significant Difference (LSD) test at the 5% significance level. The correlation between C-organic, soil pH, soil temperature, soil moisture content, stalk dry weight, and weight of corn kernels with C-mic was tested by correlation test. The results showed that the application of humic acid and TSP fertilization had no significant effect on C-mic, and there was no interaction between the two at seven days after planting (DAP), 56 DAP, and 104 DAP. There was a correlation between soil organic carbon 7 DAP (r: 0.34*), 56 DAP (r: 0.59*), and 104 DAP (r: 0.53*), soil moisture content at 7 DAP (r: 0.36*), soil pH at 56 DAP (r: 0.42*) and 104 DAP (r: 0.43*), soil temperature at 104 DAP (r: -0.52*), stalk dry weight at 56 DAP (r: 0.34*), corn kernels weight at 113 DAP (r: 0.65*) with C-mic.